PEMILIHAN MEDIA PEMBELAJARAN UNTUK MENINGKATKAN EFFEKTIFITAS PEMBELAJARAN MATA DIKLAT KEJURUAN DI SMK KOMPETENSI KEAHLIAN TEKNIK KENDARAAN RINGAN - Rabiman Rabiman (Jurnal Taman Vokasi, 2013)
Purposes of teaching and learning process in schools is to make the students learn about the subyek that has been determined by the curriculum. Teachers as learners serves to direct the students learn about the subyek specified in the curriculum. Cause it between teachers and students should have taken place two-way communication. Learning that occurs in the communication between teachers and students learning media is necessary. There are a variety of instruction media that can be used in teaching subjects in the field of Automotive engineering. Therefore, teachers should be able to select appropriate instruction media. In selecting instructional media, teacher requires some consideration. When teachers can choose appropriate learning media, The effective instruction will be created.